Encounters with Bergson(ism) in Spain : Reconciling Philosophy, Literature, Film and Urban Space - Fraser, Benjamin (Book collections on Project MUSE., 2010)
Driven by a dual analysis,Encounters with Bergson(ism) in Spainlooks at French philosopher Henri Bergson (1859-1941) in Spain--his more or less direct influence on Spanish letters--and also at Bergsonism in Spain--the more indirect resonance with his methodological posture--articulated through Spanish texts as well as theoretical approaches to film and urban space. Through this twin investigation, one part historical and the other part methodological, Benjamin Fraser seeks to broaden the scope of interest in Bergson's philosophy, to emphasize the interdisciplinary nature of Bergson's thought, and to insist upon the relevance of Bergson's methodological premise to two of the most important cultural studies disciplines today--film studies and urban geography.Following an eclectic and interdisciplinary methodology that the French philosopher himself advocated, Fraser reconciles works by some of the most notable twentieth-century authors and critics with compelling aspects of Bergsonism. From novelists Pio Baroja, Miguel de Unamuno, Juan Benet and Belen Gopegui to filmmakers Victor Erice (El sol del membrillo), Alejandro Amenabar (Abre los ojos) and Carlos Saura (Taxi), as well as urban theorists Henri Lefebvre and Manuel Delgado Ruiz, this work takes up philosopher Gilles Deleuze's call for a "return to Bergson," pushing past the established boundaries of interdisciplinary to what lies beyond.Fans of Bergson from all disciplines will also be eager to read English translations of Bergson's lectures at the Ateneo in Madrid the 2nd and 6th of May 1916, included here as an appendix.